(untitled) (Kerala Journal of Psychiatry, 2020)
The diagnosis and boundaries of borderline intellectual functioning (BIF) lack clarity. The nosological status in DSM 5 and ICD 10 and 11 are also dubious. The provision of ’borderline disability’ of 25 % for the category of Intellectual Disability, in the RPWD (Rights of persons with disability) act, falls below the benchmark disability criteria. The Kerala State commissioner for persons with disabilities categorises those with IQ between 70 and 84, as ’borderline intelligent’ and provides the benefits of scribe/interpreter to them. Can the psychiatrist certify an entity which does not exist in the current classificatory systems? The author tries to highlight the fallacies in the implementation of disability provisions in Kerala for students with BIF and provides alternative solutions vis a vis the disability plea.